Considering The Use of Mobile Application in Psychotherapy within The Framework of Ethics - Buse SENCAN (Yaşam Becerileri Psikoloji Dergisi, 2021)
Technological developments have enabled the use of online methods and mobile applications as a form of communication in clinical applications. The rapid increase and use of mobile health technology applications have not only provided many functions to be integrated into psychotherapy but also caused the emergence of new ethical implications for the use of these applications. There are no ethical guidelines or laws regarding the use of these mobile mental health applications integrated into the psychotherapy process. In this context, in the light of the relevant literature, the usage areas of mobile applications in psychotherapy were mentioned and the ethical consequences and dilemmas of using mobile applications in psychotherapy have been reviewed. These ethical implications are classified under the headings of confidentiality and data security, competence, and informed consent. Within the scope of this article, the use of mobile (mental) health applications in psychotherapy are handled within the framework of ethical rules, and it is aimed to determine the ethical problems that may be caused by the use of mobile applications in psychotherapy and to determine the points to be considered preventing the emergence of problems. Mobile health applications are used for various purposes in the psychotherapy process/clinical applications, for evaluation of symptoms, psycho-education, and monitoring of treatment progress. It seems so important for professionals considering using mobile health applications as a part of their psychotherapy applications to consider the possible ethical issues caused by mobile application use. Within this scope in this article various suggestions are given for the ethical issues that may arise from the use of mobile applications in psychotherapy, which are discussed under the titles of confidentiality and data security, competence and informed consent.